Human Factors and Pedagogic Principles to Design a Fire-Safety Pedagogic Game - Oliva, David; Tarkkanen, Kimmo; Haavisto, Timo; Somerkoski, Brita; Lindberg, Axel; Luimula, Mika (United States, 2025)
A previous study using virtual reality demonstrated that children didn’t know how to efficiently exit a building with smoke on the corridors. Fire safety is important, and as such, it should be taught in Finnish schools by kids with ages 10 – 16. However, materials are not harmonized and at the end each school is free to decide how and how much their study programs include fire safety. With the aim of creating a useful and effective pedagogic tool for teachers, we designed and created an educational game to instil the knowledge, skills and attitudes related to fire safety that kids should have. The design was done together with fire inspectors and a pedagogy expert in the field. Human factors of children as players and five pedagogic design principles were considered. The outcome was a free-to-play mobile game called Virpa – Fire Expert which was provided for iOS and Android devices. The game provides several hours of gameplay via numerous tasks and minigames, and it achieved exceptionally good player retention rates. The most innovative and pioneering aspect in the game was the combination of virtual and real worlds in the same digital learning environment via machine vision algorithms and augmented reality functionalities. Furthermore, the game was conceived as a research tool, as we wanted to evaluate the impact of the tool on the overall learning process, but also, to provide teachers, educators, and parents, with feedback about the learning outcomes of their pupils or children. Always respecting young players’ privacy, the game collects anonymously metrics and data points, which were combined in an efficient and effective evaluation form. The design of the form considered a total of seven human factors related to teachers needs and interests. The form is also free to access via a website which collects real-time data from the server and automatically organizes it for the teacher. This paper describes the applied design principles and the considered human factors regarding children, the typical walkthrough in the game, the type of collected data, the game engagement, the learning impact assessment, and the final verification tool created for teachers and educators.ame engagement and learning impact assessment results, and the final verification tool created for teachers and educators.
Human Factors in Virtual Environments and Game Design : Proceedings of the 15th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Nice, France 24-27 July 2024